2018
DOI: 10.1017/s1368980018000290
|View full text |Cite
|
Sign up to set email alerts
|

What factors may contribute to sex differences in childhood obesity prevalence in China?

Abstract: Objective Previous studies in China showed large sex differences in childhood overweight and obesity (ow/ob) rates. However, limited research has examined the cause of these sex differences. This study aimed to examine individual and parental/familial factors associated with sex differences in childhood ow/ob rates in China. Design Variables associated with child weight status, beliefs and behaviors, and obesity-related parenting practices were selected to examine their sex differences and association with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
49
3
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 36 publications
(47 reference statements)
10
49
3
4
Order By: Relevance
“…stunting. e findings are consistent with the literature as studies suggest overweight or obesity is more prevalent in urban than in rural areas [32][33][34][35], trends uncommon across the globe, and unique to the country of China. Surprisingly, subjects in a small-medium city had the highest rate of underweight and second-highest rate of overweight or obesity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…stunting. e findings are consistent with the literature as studies suggest overweight or obesity is more prevalent in urban than in rural areas [32][33][34][35], trends uncommon across the globe, and unique to the country of China. Surprisingly, subjects in a small-medium city had the highest rate of underweight and second-highest rate of overweight or obesity.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings also suggest that boys were more likely than girls to be overweight or obese [33-35, 41, 42]. A good understanding of the factors, such as weight management behaviors, weight perceptions, body image, and food parenting behaviors, that contribute to the sex differences in overweight or obesity will shed light to guide intervention efforts [42,43]. Investments in the early years of childhood can be effective in reducing gender inequality in nutritional health in China.…”
Section: Discussionmentioning
confidence: 72%
“…In one study, mothers and children had 77.1% agreement in their perception of the child’s weight status, and about 10% of children and their mothers underestimated the weight status of the child . In particular, several studies have found that Chinese boys are more likely to underestimate their weight status than girls . Girls are more likely to be sensitive to their body size and have greater discrepancies between current weight and desired weight than boys in general .…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the prevalence of excess weight appear after childhood, suggesting that growth pattern and hormonal changes play a role, which is also supported by the fact that similar or even higher prevalence is reported in girls at younger age groups . Sex differences may also be related to life‐style factors and beliefs in children and their parents . Previously, we have shown that unhealthy eating habit was more common in boys than in girls, while typically boys are more physically active at this age providing no simple explanation for the phenomenon.…”
Section: Discussionmentioning
confidence: 88%
“…41 Sex differences may also be F I G U R E 2 Effect size comparison of the Fin-HIT suggestive SNPs for BMIz in adult population and in young children related to life-style factors and beliefs in children and their parents. 42 Previously, we have shown that unhealthy eating habit was more common in boys than in girls, 28 while typically boys are more physically active at this age 43,44 providing no simple explanation for the phenomenon.…”
Section: Top Snps Related To Bmi Z-score and Waist-toheight Ratio Imentioning
confidence: 93%